2016
DOI: 10.1128/mbio.02160-15
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Diversity of Vibrio cholerae Associated with Endemic Cholera in Mexico from 1991 to 2008

Abstract: An outbreak of cholera occurred in 1991 in Mexico, where it had not been reported for more than a century and is now endemic. Vibrio cholerae O1 prototype El Tor and classical strains coexist with altered El Tor strains (1991 to 1997). Nontoxigenic (CTX−) V. cholerae El Tor dominated toxigenic (CTX+) strains (2001 to 2003), but V. cholerae CTX+ variant El Tor was isolated during 2004 to 2008, outcompeting CTX− V. cholerae. Genomes of six Mexican V. cholerae O1 strains isolated during 1991 to 2008 were sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 49 publications
0
22
0
1
Order By: Relevance
“…The classical biotype responsible for previous pandemics has been increasingly rare, and it has not been isolated from Asia or Africa after 1992 (7). A recent series of retrospective studies have reported the discovery of classical, prototype El Tor, atypical El Tor, and nontoxigenic O1 strains with some unusual genetic features in Mexico from 1983 to 2008 (710). The latest of these studies, recently published in mBio , reports the comparative genomic and phylogenetic analysis of these various biotypes (8).…”
Section: Commentarymentioning
confidence: 99%
See 3 more Smart Citations
“…The classical biotype responsible for previous pandemics has been increasingly rare, and it has not been isolated from Asia or Africa after 1992 (7). A recent series of retrospective studies have reported the discovery of classical, prototype El Tor, atypical El Tor, and nontoxigenic O1 strains with some unusual genetic features in Mexico from 1983 to 2008 (710). The latest of these studies, recently published in mBio , reports the comparative genomic and phylogenetic analysis of these various biotypes (8).…”
Section: Commentarymentioning
confidence: 99%
“…The article (8) describes a rare instance where a large variety of O1 strains are found to cohabitate outside of southern Asia. This diversity is remarkable because cholera was absent from Mexico for at least a hundred years until the 1991 Latin American epidemic.…”
Section: How To Interpret the Striking Biotype Diversity Of Mexican Vmentioning
confidence: 99%
See 2 more Smart Citations
“…In Mexico in 1991, the first epidemiological outbreak by V. cholerae O1 was registered (Choi et al . ), and to date sporadic cases are still detected (SSA, ); also, in 2003–2004 the first epidemiological outbreak caused by V. parahaemolyticus was identified (Cabanillas‐Beltrán et al . ).…”
Section: Introductionmentioning
confidence: 99%